2017
DOI: 10.3847/2041-8213/aa8cc6
|View full text |Cite
|
Sign up to set email alerts
|

Minor Contribution of Quasars to Ionizing Photon Budget at z ∼ 6: Update on Quasar Luminosity Function at the Faint End with Subaru/Suprime-Cam

Abstract: We constrain the quasar contribution to cosmic reionization based on our deep optical survey of z ∼ 6 quasars down to z R = 24.15 using Subaru/Suprime-Cam in three UKIDSS-DXS fields covering 6.5 deg 2 . In Kashikawa et al. (2015), we select 17 quasar candidates and report our initial discovery of two low-luminosity quasars (M 1450 ∼ −23) from seven targets, one of which might be a Lyα emitting galaxy. From an additional optical spectroscopy, none of the four candidates out of the remaining ten turn out to be g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
62
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 37 publications
7
62
2
Order By: Relevance
“…Haiman & Loeb 1998;Madau et al 1999). If quasars are primarily responsible, they must exist in greater numbers than the current high-redshift quasar luminosity function suggests (Onoue et al 2017;McGreer et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Haiman & Loeb 1998;Madau et al 1999). If quasars are primarily responsible, they must exist in greater numbers than the current high-redshift quasar luminosity function suggests (Onoue et al 2017;McGreer et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Determination of the quasar luminosity function at z 5.5 has constrained the contribution of quasars to the cosmic reionisation of hydrogen (e.g. Onoue et al 2017;Kulkarni et al 2018). Used as the most distant beacons of light in the Universe, quasars are also an invaluable tool to study the intervening material in absorption.…”
Section: Introductionmentioning
confidence: 99%
“…at z ∼ 2 (Harrison et al 2012), and at z ∼ 6 (Maiolino et al 2012;Cicone et al 2015). X-ray observations have also indicated that faint QSOs may play an important role in reionising the Universe (Giallongo et al 2015;Onoue et al 2017;Ricci et al 2017).…”
mentioning
confidence: 99%